2022
DOI: 10.3390/molecules27061779
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Mathematical Modelling of Factors Influencing Carbon Dioxide Absorption into the Aqueous Solution of Monoethanolamine and 1-Butyl-3-methylimidazolium Dibutylphosphate Using Response Surface Methodology (RSM)

Abstract: This paper investigated the solubility of carbon dioxide (CO2) in an aqueous solution of monoethanolamine (MEA) and 1-butyl-3-methylimidazolium dibutylphosphate ((BMIM)(DBP)) ionic liquid (IL) hybrid solvents. Aqueous solutions of MEA-(BMIM)(DBP) hybrid solvents containing different concentrations of (BMIM)(DBP) were prepared to exploit the amine’s reactive nature, combined with the IL’s non-volatile nature for CO2 absorption. Response surface methodology (RSM) based on central composite design (CCD) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Additionally, the maximum increasing impact of the dependent factor was 0.0007775, related to the interaction between L c and L d parameters. The coded parameters in the quadratic model were beneficial for predicting the relative significance of the factors by comparing the coefficients of the factors [86]. By default, the factors' low and upper levels were coded as −1 and +1, respectively [66].…”
Section: Mathematical Model Fitting and Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the maximum increasing impact of the dependent factor was 0.0007775, related to the interaction between L c and L d parameters. The coded parameters in the quadratic model were beneficial for predicting the relative significance of the factors by comparing the coefficients of the factors [86]. By default, the factors' low and upper levels were coded as −1 and +1, respectively [66].…”
Section: Mathematical Model Fitting and Assessmentmentioning
confidence: 99%
“…By default, the factors' low and upper levels were coded as −1 and +1, respectively [66]. The coded equations were useful for understanding the relative effects of the parameters by comparing the coefficients of the factors [86]. In contrast, Equation (13) with actual factors specified in original units was used for predictions in the original factor units.…”
Section: Mathematical Model Fitting and Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that the longer alkyl chain in the dibutylphosphate anion creates a larger free volume to accommodate more CO 2 molecules. Azhar et al investigated the solubility of CO 2 in an aqueous solution of monoehanolamin and 1–butyl–3–methylimidazolium dibutylphosphate (BMIM·DBP) ionic liquid hybrid solvents [ 17 ]. Based on response surface methodology (RSM) and mathematical modelling, they predicted the optimum conditions for CO 2 absorption.…”
Section: Introductionmentioning
confidence: 99%